PREVENTION OF COMPLICATIONS OF DENTAL CARE IN MEDICAL INSTITUTIONS - Musurmanov Fazliddin; Hayitboev Zafar; Muratova Saodat Kadirovna (Journal of new century innovations, 2024)
Annotation. One of the most common modern therapeutic dentistry – reduction of dental diseases among children and adolescents. In maintaining dental health in the future generation leading role of playing parents. Copying adult behavior is an accounting part of children's bank accounts. Image parents' lives, their habits and skills, dental knowledge and Health indicators influence dental addiction child status.